Família Lauraceae: aspectos importantes na produção de metabolitos secundários com potenciais aplicações na sociedade - Sorratini, Bruno Siqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The field of natural products is constantly growing, due to all the options of plant applications that can be studied and the number of species whose information on their chemical constituents is not yet known. The Lauraceae family is a group of plants containing species mostly present in South America. In this family several popular plants such as avocado and cinnamon are included, as well as others with few chemical studies. Nine extracts from five different species of this family (Ocotea odorifera, Ocotea megabotamica, Ocotea pulchella, Nectandra membranaceae and Endlicheria paniculata) were collected from three different reserves present in the state of São Paulo. Through HPLC (High Performance Liquid Chromatography), NMR (Nuclear Magnetic Resonance) and EM (Mass Spectrometry) analysis, compounds were annotated and clusters were built comparing each extract. Data were analyzed both to identify the effect of different environmental media on the production of metabolites of these species, as well as new compounds in the family. Lauraceae has several compounds with applications in medicine, agriculture and food, some resulting from the environmental pressures where the plant is found and others that have no reports in the family.

A área de produtos naturais cresce constantemente, devido a todas as opções de aplicações de plantas que podem ser estudadas e à quantidade de espécies cuja informação dos constituintes químicos, ainda não é conhecida. A família Lauraceae é um grupo de plantas contendo espécies presentes majoritariamente na América do Sul. Nesta família várias plantas populares como abacate e a canela estão inseridas, assim como outras com poucos estudos químicos. Nove extratos de cinco espécies diferentes desta família (Ocotea odorífera, Ocotea megabotamica, Ocotea pulchella, Nectandra membranaceae e Endlicheria paniculata) foram coletados em três reservas diferentes presentes no estado de São Paulo. Por meio de análises por CLAE (Cromatografia liquida de alta eficiência), RMN (Ressonância magnética nuclear) e EM (Espectrometria de massas) foram anotados compostos e construídos clusters comparando cada extrato. Os dados foram analisados tanto para identificar o efeito dos diferentes meios ambientais na produção de metabolitos dessas espécies, bem como compostos inéditos na família. Lauraceae possui diversos compostos com aplicações na medicina, agricultura e alimentação, alguns resultado das pressões ambientais onde a planta se encontra e outros que não possuem relatos na família.
Lauraceae Family: important aspects of the secundary metabolite production with potential applications in society
Keywords: Lauraceae; Cromatografia líquida de alta eficiência; Ressonância magnética nuclear; Mutação de plantas